God’s People Struggle and Justice: An Exposition Review Amos 1: 1-15 - Bobby Kurnia Putrawan (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Abstract. This article aimed to show God's justice in the midst of lives of His people. The method used is the historical and grammatical exposition of Amos 1: 1-15. The struggle of faith of God's people is never loose in sorrow, sadness, and cheering. In the book of Amos 1: 1-15 teaches us that the people's struggle is inseparable from God's justice. God gives protection to His people to pass through every issue or problem of life. God also does His justice both to good doers and condemnation to those who do evil. Thus every people should live what God promised and hold in hope in God.